Alakbarova, Lala - (:unkn) unknown (My University, 2026)
Lala Aziz Alakbarova graduated from the Azerbaijan Institute of National Economy, Faculty of Planned Economy, in 1989 with a degree in Labour Economics and Sociology. From 1985 to 1986, she worked at the Offshore Exploration Drilling Department of Kaspburneftegazprom. Since 1986, she has been employed at the Department of Business Economics and Management of the Azerbaijan University of Architecture and Construction, where she has held the positions of laboratory assistant, senior laboratory assistant, lecturer, and senior lecturer. Lala Aziz Alekperova is the author of 25 educational curricula, one methodological manual, one textbook, and approximately 100 scientific publications. She also serves as the Executive Secretary of the Construction Economics and Management Scientific and Practical Journal, published by the Department of Business Economics and Management. Her research interests include management, accounting, taxation, and tax administration.